(3cJGH ajg CSeGA GdQLGd GdPjf hQO PcQge aj GdegPH ddTjQGRis - (3CHhGdeMGSf jhSa Hf QGaYs; (3EHQGgje Hf eMeO Hf EHQGgje GdTjQGRj,J (B1070 (3g` s
(3ChdgG (B:s
(3bGd SjOfG hehdGfG bGVi GdbVGI CHhGdeMGSf jhSa Hf QGaY Hf Jeje s
(3JHUQI GdYfhGf (B:s
(3GNJjGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B67s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B212 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs